DIABETES MELLITUS AND CONCURRENT RENAL INSUFFICIENCY AS PROGNOSTIC INDICATORS FOR ACUTE MYOCARDIAL INFARCTION - kumar, Dr Rajeev (Student's Journal of Health Research Africa, 2023)
Background: Prognostic factors for acute myocardial infarction include diabetes mellitus and renal im- pairment (AMI). Few studies, meanwhile, have examined the impact of renal insufficiency in the setting of diabetes and AMI. Here, we looked into the clinical outcomes for individuals with AMI who also had renal impairment and diabetes mellitus. Method: 400 AMI patients (62 ± 12 years; 71% men) were included in this study from March 2022 to February 2023 and divided into 4 groups as follows: Group I (n = 100) did not have either diabetes or renal insufficiency (glomerular filtration rate [GFR] 50 ml/min/1.72m2), Group II (n = 100) did not have either condition, Group III (n = 100) did not have either condition but did have renal insufficiency, and Group IV (n = 100) did. Major adverse cardiac events included myocardial infarction, target lesion revascularization, and coronary artery bypass graft. Results: 180 (18.1%) patients experienced the primary objectives. In terms of composite MACE, there were differences between the 4 groups that were statistically significant (Group I: 12.4%; Group II: 15.6%; Group III: 30.4%; Group IV: 36.6%; p <0.002). The 12-month mortality increased stepwise from Group III to IV as compared with Group I in a Cox proportional hazards model after multiple covariates were taken into account (hazard ratio [HR], 1.95; 95% confidence interval [CI], 1.33-2.85; p = 0.002; and HR, 2.41; 95% CI, 1.61-3.61; p <0.002, respectively). However, Kaplan-Meier analysis found no significant difference between Group III and IV in the chance of mortality at 1 year (p = 0.287). Conclusion: Composite MACE is linked to renal insufficiency, particularly in conjunction with diabetes, and implies a bad prognosis in individuals with AMI. Patients with diabetes and/or renal insufficiency are classified, which is useful data for early risk stratification of AMI patients.